Systems for the Assessement of a Severe Injuried Limb. Suitability in the Modern War (Literature Review) - Liabakh, A.P. (TERRA ORTHOPAEDICA, 2023)
Summary. The review of the literature is devoted to the consideration of systems for assessing a seriously injured (mangled) extremity and their suitability in combat conditions: HFS-57, MESI, PSI, LSI, MESS, NISSSA, GHOISS, MUES. A search was carried out on the PubMed database for the period 1578-2023. Advantages and disadvantages are shown. The most used for combat limbs injury is MESS.